Shifting paradigms in the management of pediatric differentiated thyroid cancer from static to dynamic risk stratification: a step forward toward precision medicine - Ajdari, Sadegh Ebrahim; Shafiei, Babak; Motazedian, Motahareh; Qutbi, Mohsen; Esmaeilzadeh, Paridokht; Asli, Isa Neshandar; Javadi, Hamid; Assadi, Majid (Nuklearmedizin - NuclearMedicine, 2019)
Introduction This study aimed to assess the usefulness of a risk-adopted management system known as dynamic risk stratification (DRS) in comparison with the American (ATA) and European Thyroid Associations’ (ETA) risk classifications in the management of pediatric patients with differentiated thyroid cancer (DTC).Materials and Methods The current study included 50 pediatric patients with DTC who were treated with total or near total thyroidectomy and radioiodine ablation whose risk assessment was initially defined according to the ATA and ETA guidelines. During the two years after initial treatment, patients were reclassified according to their DRS.Results The study showed that the ability of the DRS system to predict the final outcome was superior to that of the ATA and ETA guidelines. The observed variance in predicting final outcome was 2.3 % for ETA, 14.8 % for ATA, and 83.4 % for DRS. In intermediate/high-risk patients, according to the ATA/ETA guidelines, an excellent response to initial therapy resulted in a noteworthy reduction (about 40 %) for detection of structural disease at the time of final follow-up. The risk of structural disease at the time of final follow-up was significantly higher in the structural incomplete response group (HR = 23.34, P = 0.00) and biochemical incomplete response group (HR = 13.83, P = 0.03) than in the excellent response group.Conclusion The data documented the significance of re-stratifying pediatric patients with DTC on the basis of the findings obtained at the time of or after their initial therapy (total thyroidectomy and radioiodine ablation), predominantly in the intermediate/high-risk patients. In addition, DRS helped to better modulate the later follow-up, excluding a large number of intermediate/high risk patients from needless intensive workups, allowing personalization of follow-up management.
Keywords: Pediatric differentiated thyroid cancer; dynamic risk stratification (DRS); American Thyroid Association (ATA) guideline; European Thyroid Association (ETA) guideline